“Hot Spring for Cure of Diseases”: On the Practice of Hydropathy in the Golden Horde. - Abzalov L.F. (Золотоордынское обозрение)
Objective: Based on the achievements of hydrotherapy and balneology, the author of this article examines the practice of hydrotherapy in the Golden Horde. Research materials and results: The materials presented below largely complement our understanding of the Golden Horde’s society and shed light on such a poorly studied historical aspect of it as the history of medicine – this determines the novelty of the study. An analysis of the brief reports of the Arab authors al-‘Umari and Ibn Battuta allows us to conclude that hydrotherapy was practiced in the Golden Horde along with the active use of mineral waters for their curative properties. Hydrotherapeutic procedures were carried out in accordance with certain norms, which could be empirical or theoretical – that is, based on the works of famous doctors. Archaeological research points to the widespread use of baths that could be used for the treatment of diseases. Thus, water procedures for the treatment of various diseases were not only known in the Golden Horde, but also actively practiced there. It is possible that they were more common than was earlier considered to be the case. At the same time, it should be pointed out that healing and mineral water springs could be found in virtually every region of the Golden Horde, and each constituent people had their own concepts regarding the “element” of water, health, and what constituted a healthy lifestyle. This determined the specific methods of hydrotherapy, based on the features of a particular ethno-cultural community’s worldview.